Tomato Quality from Organic and Conventional Production in the Selected Area of Dharan, Sunsari, Nepal - Yadav, Pramod Kumar (International Journal of Applied Sciences and Biotechnology, 2017)
From the selected area of Dharan, Sunsari, Nepal, conventional and organic tomatoes were grown and tested with different parameters. Conventional tomatoes contained less value of Mg, Ca, K, Cu and Mn, but more value of Fe than organic tomatoes, where as Pb and Ni were not detected.The Zn was found to be same in both tomatoes sample. The sizes of conventional tomatoes were reportedly bigger than organic tomatoes. The viscosity and surface tension of organic tomatoes juice were reported to be higher than in conventional tomatoes juice. The refractive index value was found to be lower in conventional tomatoes juice than in organic tomatoes juice. The vitamin C value was found to be higher in conventional tomatoes juice than in organic tomatoes juice. The comparative study of color, juice containing capacity, storage capacity and firmness of organic and conventional tomatoes of Dharan,Sunsari,Nepal has also been included. Int. J. Appl. Sci. Biotechnol. Vol 5(1): 91-97